Counseling on Organic Fertilizers in Increasing Agricultural Productivity in Bangunkarya Village - Tati Kartini; Muhammad Ruda’i; Renaldi Hidayat; Ridwan Fauzi; Neneng Nurmalasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Increasing the productivity of agricultural products is the hope for all farmers with maximum results. The use and price of fertilizers are the main constraints in plant care. Through outreach activities involving the Bangunkarya village government, the Agriculture Service and farmer groups provide understanding and benefits of using organic fertilizers. Organic fertilizers are fertilizers derived from livestock manure which are processed with certain ingredients so that they can become ready-to-use fertilizers for agricultural land. This community service uses the PAR (Participatory Action Research) method by observing as well as participating in the community. Then carry out the STITNU Al Farabi Pangandaran KKN-PAR work program in 2023 which starts on 3 February 2023 to 3 March 2023. The results of the counseling and fertilizer production program in Bangunkarya village are cultivating the use of organic fertilizers.